Pengembangan E-Modul Berbasis Flip PDF Professional Pada Materi Dinamika Gerak Partikel - Wijaya, Silvia Anggri (Journal of Health, Education, Economics, Science, and Technology, 2025)
This study aims to evaluate the feasibility of an e-module based on Flip PDF Professional, focusing on media and material experts' assessments as well as student responses. The study employs a 3-D model, a modified version of the 4-D research and development method, consisting of Define, Design, and Develop stages. The instruments used include product assessment sheets and response questionnaires. Data analysis for testing the product feasibility and student responses uses standard scales. The findings indicate that the developed product, an e-module based on Flip PDF Professional covering the topic of particle motion dynamics, is highly feasible for use in physics instruction. The media received an average score of 3.54, and the material scored 3.63 based on evaluations from media and material expert validators. Furthermore, the e-module's assessment in the limited trial, based on student responses, resulted in an average score of 3.61, indicating that the response to the e-module was very positive.